Numerical and experimental analysis of the shear capacity of interconnected concrete block walls - Oliveira, Luciane Marcela Filizola de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
Predicting the behavior of interconnected masonry walls is a challenging issue, given the influence of a wide range of factors, such as the mechanical properties of the materials (blocks and mortar) and the way the walls are connected to each other. In this paper, experimental results in H-shaped walls subjected to shear at the vertical interface are introduced with a numerical representation. Concrete blocks and two types of connections (running bond and U-steel anchors) were considered in the tests. Computational modelling was carried out using the Diana® FEM software to complete the study and understand the structural behavior of the masonry panels. The influence of the bonding pattern on the experimental and numerical response was studied and good agreement between the results was found. Moreover, the numerical analysis showed that the computer models of the interconnected walls adequately represented the behavior of the physical models regarding load capacity and cracking patterns.